Employability skills - Hind, David, ....-; Moss, Stuart, ....- (Sunderland : Business Education Publishers, 2007)
All students in further and higher education need to develop their employability skills. These skills are frequently specified by employers in the job advertisements they publish to recruit new employees from colleges and universities. At the job recruitment and selection stage employers pay careful attention to ensure that the young people they recruit are able to: communicate orally and in writing, work as a member of a group, solve problems, manage projects, handle and manipulate data, gather information.